PERANCANGAN ALAT PENGENDALI SUHU RUANGAN SERVER MENGGUNAKAN SENSOR LM35 DENGAN INFORMASI SMS BERBASIS ATMEGA16 - Septian Anwar, Rian (Yayasan Akrab Pekanbaru, 2019)
The server is a computer systems that provide the type of certain services to client in a computer network. The temperature is magnitude whose said the degree of heat cold an object and an instrument used to measure the temperature is a thermometer. Room temperature, in scientific use, is considered far less more between 20 to 25 degrees centigrade although the value of are not a value determined by exactly. To ease calculation , often used 20 points c or 300 k. A solution that arises from the issue was the method design instrument monitoring room temperature server means of sensors and give notification to user through services sms ( short message service ). Design instrument control room temperature server means of sensors lm35 based mikrokontroler atmega 16 is an apparatus used for control room temperature server to avoid possible overheat on server. The addition of censorship lm35 functioned to detect room temperature , while module sim800l work to send sms to the operator , if the temperature exceeds the limit of which have been determined on program , fan will take an ototmatis lighted so that server room to return to normal. The application of the control system room temperature server means of sensors lm35 based mikrokontroler atmega 16 equipped with sensors lm35 and module sim800l installed in the room server , expected to facilitate control room server to avoid possible overheat.